Pencarian Rute Terpendek Dalam Pendistribusian Darah di Palang Merah Indonesia (PMI) dengan Algoritma Dijkstra - Hidayatullah, Catur; R, Rakhmat Kurniawan; Armansyah, Armansyah (TIN: Terapan Informatika Nusantara, 2024)
The Indonesian Red Cross (PMI) is an independent and neutral organization in Indonesia engaged in humanitarian activities. One of the departments within the Indonesian Red Cross is the blood donor unit. The Blood Donor Unit (UDD) of PMI Deli Serdang is one of the Indonesian Red Cross offices in the Deli Serdang district, which deals with social humanitarian activities such as blood donation, volunteer recruitment, emergency response, and others. One common issue in blood distribution is the numerous routes that need to be taken, resulting in wasted time and delayed blood deliveries. Due to this issue, the implementation of artificial intelligence is needed to determine the shortest route for optimal and fast blood delivery. The application of artificial intelligence in problem-solving in the field of computer science has seen rapid development over the years in line with the advancement of artificial intelligence itself. In determining the shortest route, several algorithms can be used, one of which is the Dijkstra algorithm. It is used to solve problems in a graph to determine the shortest route. In the process, the Dijkstra algorithm determines the points that will become the distance weights connected from one point to another, resulting in the desired nodes. Therefore, an application is needed to find the nearest route to make blood delivery more time-efficient. In manual calculations using the algorithm, it was found that the shortest route from UDD (PMI Deli Serdang Blood Donation Unit) to GM (Grand Medistra Hospital) is through the route UDD → A → B → C → D → GM = 0 + 300 m + 250 m + 1,500 m + 35 m + 90 m with a total distance of 2,175 meters or 2.1 kilometers in 5 minutes. Thus, the use of the Dijkstra algorithm can assist in determining the fastest and optimal route for blood distribution, saving time and improving delivery efficiency.